Indústria cultural, semiformação e as metamorfoses no conceito de infância - Motta, Gabriela Massuia (Universidade Federal de São Carlos, 2010)
The present work, based on concept of Hallbildung, brought as Critic Theory, it analyze the change of the concept of childhood post modern, it trying understand the condition caused the your supposed disappear, and more that this, it trying found the caused this change of the present society subjugate to Cultural Industry. Besides of this, knowing that the concept it make of the childhood is direct linked to the concept of the adult life, this results cause the subjective traformation like all, it make an experiment to find out the cause possible that Postman named of the adult-child, and prolong this phase agree whit dissatisfied narcisic wish and the weak self for orders of the Cultural Industry making to formation of the falseindividual.
Keywords: Educação; Teoria crítica; Indústria cultural; Semiformação; Adulto-criança; Cultural industry; Hallbildung; Adult-child; CIENCIAS HUMANAS::EDUCACAO